Ezra Ayers Carman papers - Carman, Ezra Ayers, 1834-1909.
Correspondence, drafts of chapters, notes, printed material, maps, and other papers comprising Carman's book file for his history of the American Civil War. Subjects include campaigns in Maryland, Tennessee, Virginia, West Virginia, the Potomac River, and the Shenandoah Valley; Abraham Lincoln and his relations with George Brinton McClellan and other Union officers; secession and the secession convention in Virginia; and slavery.
Microfilm edition available, in part
Microfilm produced from originals in the Manuscript Division.
Library of Congress Geography and Map Division.
Library of Congress Serial and Government Publications Division.
U.S. Army officer, civil servant, and author.
Collection material in English.
Keywords: Lincoln, Abraham, -- 1809-1865.; McClellan, George Brinton, -- 1826-1885.; United States. -- Army -- Officers; Secession -- Southern States; Secession -- Virginia; Slavery -- United States; Maryland -- History -- Civil War, 1861-1865 -- Campaigns; Potomac River -- History; Shenandoah River Valley (Va. and W. Va.) -- History; Tennessee -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; West Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Army officers; Authors; Civil servants